Synthesis and characterization of doped and undoped nano-columnar DLC coating - Foo, Jin Hoe (Penerbit UTM Press, 2013)
Amorphous carbon (a-C:H/a-C) or Diamond-like carbon (DLC), has a very high potential diverse engineering and medical application for high wear resistance and tribological performance. Naturally grown columnar DLC films were chemically modified by post-treatment via electron beam irradiation (EB-irradiation). Precise observation and characterization is carried out by field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), and Raman spectroscopy. This nano-columnar a-C:H film has a unique nano-structure and mechanical properties which composed of graphitic inter-columnar network with amorphous carbon columns. Metallic doping into the inter-columns reflects positively on mechanical response by chemical modification with physical hardening.